Evaluation of the Antimicrobial Activities of Plant Oxylipins Supports Their Involvement in Defense against Pathogens - Prost, Isabelle (American Society of Plant Biologists, 2005)
Plant oxylipins are a large family of metabolites derived from polyunsaturated fatty acids. The characterization of mutants or transgenic plants affected in the biosynthesis or perception of oxylipins has recently emphasized the role of the so-called oxylipin pathway in plant defense against pests and pathogens. In this context, presumed functions of oxylipins include direct antimicrobial effect, stimulation of plant defense gene expression, and regulation of plant cell death. However, the precise contribution of individual oxylipins to plant defense remains essentially unknown. To get a better insight into the biological activities of oxylipins, in vitro growth inhibition assays were used to investigate the direct antimicrobial activities of 43 natural oxylipins against a set of 13 plant pathogenic microorganisms including bacteria, oomycetes, and fungi. This study showed unequivocally that most oxylipins are able to impair growth of some plant microbial pathogens, with only two out of 43 oxylipins being completely inactive against all the tested organisms, and 26 oxylipins showing inhibitory activity toward at least three different microbes. Six oxylipins strongly inhibited mycelial growth and spore germination of eukaryotic microbes, including compounds that had not previously been ascribed an antimicrobial activity, such as 13-keto-9(Z),11(E),15(Z)-octadecatrienoic acid and 12-oxo-10,15(Z)-phytodienoic acid. Interestingly, this first large-scale comparative assessment of the antimicrobial effects of oxylipins reveals that regulators of plant defense responses are also the most active oxylipins against eukaryotic microorganisms, suggesting that such oxylipins might contribute to plant defense through their effects both on the plant and on pathogens, possibly through related mechanisms.